Influence of biased feedback on performance in a Vernier discrimination task - Yang, Chenfan; Xu, Ziran; Zhong, Yaoyao; Wang, Tianze (Frontiers in Psychology, 2023)
The influence of feedback on performance is controversial. It has been found to be ineffective, beneficial, or harmful in previous studies. Different results may be related to the conflict between prior beliefs and sensory evidence. The present study used a vernier discrimination task to investigate the influence of biased feedback, which is the most likely type of feedback to produce conflict. Biased feedback means that the feedback and subjects' choices are inconsistent. In Experiment 1, each trial was followed by feedback, with large offset verniers as guidance. The large offset verniers always received the correct feedback but the small and medium offset verniers may receive biased feedback. In Experiment 2, feedback was provided after each block (8 verniers). Experiment 3 canceled the large offset vernier to investigate the influence of block feedback on the signal and noise. The results showed that the accuracy of target vernier decreased due to biased feedback in both the trial feedback (experiment 1) and block feedback (experiment 2). However, in Experiments 1 and 2, the performance rebounded after the absence of feedback. Moreover, If the difference between the two types of stimuli is high, encoding learning rather than decision learning will occur (experiment 1 and 2). If the discrimination between the two types of stimuli is low, the individual's discrimination of noise is more vulnerable than that of the signal under the influence of biased feedback (experiment 3). These results are discussed from the aspects of encoding learning, mechanism of biased feedback, monitoring of internal feedback, and generalization of false decisions.